The role of civil society organizations in monitoring legislative institutions: A survey of the opinions of a sample of citizens in the Kurdistan Region - رشيد, ساكار عزيز (Sulaimani Journal for Humanities, 2019)
The study aims to know the role played by civil society organizations in monitoring legislative institutions, and to know the extent to which civil society organizations enjoy independence and freedom. The study found that the impact of civil society organizations on the performance of legislative institutions, where the greater the control of civil society organizations on the legislative institution the better their performance, and also found that most of civil society organizations, tried to investigated the exercise of control functions of the project Parliamentary oversight objectively, and disclosed the sources of funding for their projects transparently. The study recommends that civil society organizations should monitor the performance of the legislative institution in order to improve the performance of the parliament and their access to the value of exchange between citizens and parliament by committing to their promises and electoral programs. Civil society organizations must also be independent, as they should exercise their oversight functions objectively, and disclose their project funding sources with absolute transparency.
Keywords: civil society organizations; legislative institution; Monitoring; independent; transparency